Infection Rate in Laparoscopic Surgery in Low-Resource Facilities in Bangladesh - Saha, Pankaj Kumar (Bangladesh Journal of Infectious Diseases, 2025)
Abstract Not Available Bangladesh Journal of Infectious Diseases, December 2024;11(2):235-236